KAJIAN MENDALAM TENTANG KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA NON-RUTIN SISWA - Dwi Rizki Muharani; Lalu Sucipto; Syaharuddin Syaharuddin (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to describe non-routine mathematics problem solving in relation to students' self-efficacy and math anxiety. We collect data from journal databases both national and international. The eligibility criteria are used with the keyword "non-routine mathematical problem solving" with intervals of the last 10 years. Based on the results of the synthesis, it was found that several important variables related to the topic were self-efficacy, reading comprehension, mathematic attitudes, think-aloud processes, mathematics anxiety, and truth-seeking. From these variables it was found that self-efficacy (self-confidence) and mathematics anxiety (anxiety mathematics) have an important role in solving non-routine mathematics problems